Implementing cryptography using Python - Bray, Shannon, 1972- (Wiley, 2020)
Learn to deploy proven cryptographic tools in your applications and services Cryptography is, quite simply, what makes security and privacy in the digital world possible. Tech professionals, including programmers, IT admins, and security analysts, need to understand how cryptography works to protect users, data, and assets. Implementing Cryptography Using Python will teach you the essentials, so you can apply proven cryptographic tools to secure your applications and systems. Because this book uses Python, an easily accessible language that has become one of the standards for cryptography implementation, you'll be able to quickly learn how to secure applications and data of all kinds. In this easy-to-read guide, well-known cybersecurity expert Shannon Bray walks you through creating secure communications in public channels using public-key cryptography. You'll also explore methods of authenticating messages to ensure that they haven't been tampered with in transit. Finally, you'll learn how to use digital signatures to let others verify the messages sent through your services.-Learn how to implement proven cryptographic tools, using easy-to-understand examples written in Python -Discover the history of cryptography and understand its critical importance in today's digital communication systems -Work through real-world examples to understand the pros and cons of various authentication methods -Protect your end-users and ensure that your applications and systems are using up-to-date cryptography.